Perspectives of Fc engineered antibodies in CD19 targeting immunotherapies in pediatric B-cell precursor acute lymphoblastic leukemia. (3rd August 2018) - Kellner, Christian; Peipp, Matthias; Gramatzki, Martin; Schrappe, Martin; Schewe, Denis M.
ABSTRACT: CD19 immunotherapies based on T cells opened new avenues in the treatment of pediatric B-cell precursor acute lymphoblastic leukemia (BCP-ALL). However, Fc engineered CD19 antibodies may also bear great potential. In light of recent preclinical and clinical data, perspectives of such antibodies designed for improved effectiveness in BCP-ALL are presented.